Human Capital Optimization: The Key to Improving Welfare in Rural Communities - Ardika Nanda Prakoso (Al-Qalam Institute, 2023)
The focus of this study is to explore the impact of access to information and communication, health facilities, and village fund allocation on the education level of the community in Banyuwangi Regency using a panel data regression approach. The research method used was regression panel data with three different approaches, namely Fixed Effect Model (FEM), Random Effect Model (REM), and Common Effect Model (CEM), using data from 25 sub-districts in Banyuwangi Regency during the 2016-2020 time frame. The results showed that the variables X1 (Access to Information and Communication) and X2 (Health Facilities) had a significant influence on the dependent variable at a significance level of 0.05, while the variable X3 (Village Fund) was not significant. The Fixed Effect Model (FEM) method produces different coefficients and probabilities than the Common Effect Model (CEM) and Random Effect Model (REM) methods, with the FEM model showing a significant influence of the variables X1 and X2, while the CEM and REM models showing similar results for variables X1 and X2. The implications of this study emphasize the importance of policies that support access to information and health facilities to improve the welfare of the community in Banyuwangi Regency.